2016
DOI: 10.3346/jkms.2016.31.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Markers of Oxidative Stress in Saudi Women with Recurrent Miscarriage

Abstract: This study was undertaken to investigate the antioxidant/oxidant status in recurrent miscarriage patients. Antioxidants including glutathione peroxidase (GPx), catalase (CAT), glutathione reductase (GR), reduced glutathione (GSH) and selenium (Se), as well as the oxidants hydrogen peroxide (H2O2), oxidised glutathione (GSSG) and lipid peroxidation were assayed in plasma, whole blood and placental tissue of non-pregnant women (NP), healthy pregnant women (HP), and recurrent miscarriage (RM) patients. Results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 37 publications
3
63
0
Order By: Relevance
“…79 The impaired placental development or degeneration of syncytiotrophoblast in early pregnancy may be caused by oxidative stress that leads to RSA. 81 Although reports suggest that the use of antioxidant supplements is beneficial in vitro fertilization, 82 studies related to their use in preventing miscarriage are very rare. A recent study has also found the enhanced ROS in blood and placental tissue of RSA patients.…”
Section: Mel Atonin and Recurrent S P Ontaneous Abortionmentioning
confidence: 99%
See 1 more Smart Citation
“…79 The impaired placental development or degeneration of syncytiotrophoblast in early pregnancy may be caused by oxidative stress that leads to RSA. 81 Although reports suggest that the use of antioxidant supplements is beneficial in vitro fertilization, 82 studies related to their use in preventing miscarriage are very rare. A recent study has also found the enhanced ROS in blood and placental tissue of RSA patients.…”
Section: Mel Atonin and Recurrent S P Ontaneous Abortionmentioning
confidence: 99%
“…A recent study has also found the enhanced ROS in blood and placental tissue of RSA patients. 81 Although reports suggest that the use of antioxidant supplements is beneficial in vitro fertilization, 82 studies related to their use in preventing miscarriage are very rare. Concerning the current research results, we speculate strongly that supplementary antioxidant therapy including Se, Zn, Cu, Mn, ascorbate, GSH, and αtocopherol, as well as melatonin, may be beneficial to such patients during pre-conception and the first-trimester post-conception.…”
Section: Mel Atonin and Recurrent S P Ontaneous Abortionmentioning
confidence: 99%
“…[33] The assay mixture contained sodium phosphate buffer (150 µl, pH 7.4), 8 mM EDTA (50 µl), DTNB solution (50 µl) and 2 mM NADPH (100 µl). GSH standards (20–80 µM) and fibroblast sonicates (50 µl) were then added and the tubes incubated at 37°C for 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…We first detected the number of We next quantified the decrease in circulating RBCs in homozygous mutants and their siblings. We performed a quantitative measure of total hemoglobin content using a colorimetric assay in which endogenous hemoglobin can be measured quantitatively at a wavelength of 400nm 44 . In order to measure the levels of hemoglobin in siblings and Vu57 carriers, homozygous Vu57 larval were separated according phenotype at 3 dpf 34 and the total hemoglobin content of homozygous carriers was compared to the hemoglobin content of wildtype and heterozygous siblings at 96 hpf.…”
Section: Mutations In Hmgcs1 Disrupt Rbc Developmentmentioning
confidence: 99%